2013
DOI: 10.1097/jnr.0b013e3182921f35
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Korean–Chinese Middle School Students

Abstract: The findings may help develop more effective intervention approaches to prevent adolescent smoking. Preventive programs should involve smoking parents by increasing the value they place on their children's nonsmoking behavior and equipping them to help deter adolescent smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
0
1
Order By: Relevance
“…An urgent interventional program addressing the association of smoking and obesity and their cardiovascular risk is highly needed. The reported smoking rate in the current study was lower than a percentage (24.8%) reported among students in Hungary ( 21 ) and higher than a study from China ( 22 ). In the present study, breakfast skipping is congruent with the findings of Sun et al ( 23 ) who reported a prevalence of 41.7%.…”
Section: Discussioncontrasting
confidence: 90%
“…An urgent interventional program addressing the association of smoking and obesity and their cardiovascular risk is highly needed. The reported smoking rate in the current study was lower than a percentage (24.8%) reported among students in Hungary ( 21 ) and higher than a study from China ( 22 ). In the present study, breakfast skipping is congruent with the findings of Sun et al ( 23 ) who reported a prevalence of 41.7%.…”
Section: Discussioncontrasting
confidence: 90%